A simple Newtonian toy box approach to flood flow modeling, simulation and analysis - Mansos, John Francis L.; Real, Victoria Cassandra R.; Ricio, Dustin Edric L.
Two of the most common natural calamities in the Philippines are heavy rainfall and typhoon which both result to flood. As these calamities continue to surge the country, numerous methods are created to prevent their possible damages.